Correlation-based clustering and the modified naÃ¯ve-Bayesian-classification for gene-sequence data analysis - Arputharaj, vijay; S.Sheeja, Dr.; K. Anuradha, Dr. (International Journal of Engineering and Technology, 2019)
Correlation based Clustering separates the statistical data from the most favourable amount of clusters with corresponding to the statistically analysed data points. As we know, Data mining is the technique of figuring out progression of determining patterns inside huge statistics and datasets, which concerns techniques related to connection with machine related learning, statistics and also the advanced database systems. This technique denotes the gene sequence using the novel classification technique, which improves the accuracy of classification under the course of dimensionality. Grouping the gene data using correlation-based clustering will reduce the execution time. Â Â